Light, medium-weight, or heavy? The nature of the first supermassive black hole seeds. Issue 1 (21st June 2021) - Sassano, Federica; Schneider, Raffaella; Valiante, Rosa; Inayoshi, Kohei; Chon, Sunmyon; Omukai, Kazuyuki; Mayer, Lucio; Capelo, Pedro R
ABSTRACT: Observations of hyper-luminous quasars at z >6 reveal the rapid growth of supermassive black holes (SMBHs ${\gt}10^9 \, \rm M_{\odot }$ ) whose origin is still difficult to explain. Their progenitors may have formed as remnants of massive, metal-free stars (light seeds), via stellar collisions (medium-weight seeds) and/or massive gas clouds direct collapse (heavy seeds). In this work, we investigate for the first time the relative role of these three seed populations in the formation of z >6 SMBHs within an Eddington-limited gas accretion scenario. To this aim, we implement in our semi-analytical data-constrained model a statistical description of the spatial fluctuations of Lyman–Werner (LW) photodissociating radiation and of metal/dust enrichment. This allows us to set the physical conditions for black hole seeds formation, exploring their relative birth rate in a highly biased region of the Universe at z >6. We find that the inclusion of medium-weight seeds does not qualitatively change the growth history of the first SMBHs: although less massive seeds (${\lt}10^3\, \rm M_\odot$ ) form at a higher rate, the mass growth of a ${\sim}10^9\, \rm M_\odot$ SMBH at z <15 is driven by efficient gas accretion (at a sub-Eddington rate) on to its heavy progenitors ($10^5\, \rm M_\odot$ ). This conclusion holds independently of the critical level of LW radiation and even when medium-weight seeds are allowed to form in higher metallicity galaxies, via the so-called supercompetitive accretion scenario. Our study suggests that the genealogy of z ∼6 SMBHs is characterized by a rich variety of BH progenitors, which represent only a small fraction (${\lt} 10{-}20{{\ \rm per\ cent}}$ ) of all the BHs that seed galaxies at z >15.